Unified Digital Law Enforcement Environment – Necessity and Prospects for Creation in the “BRICS Countries” - E. Nikitin; M. C. Marius (BRICS Law Journal, 2020)
The article examines the prospects for the development of an interstate association of BRICS member nations and concludes that it is necessary to expand cooperation in addition to the economic sphere through other areas, in particular, the organization of interaction to combat crime. The article focuses on the fact that an important area of joint cooperation between the BRICS member nations will be activities in the field of security and combating crime. The main promising areas of cooperation between the BRICS member nations in the field of security are formulated and forms of joint activities in these areas are proposed. This area of cooperation of the BRICS member nations should be based on modern information technologies, which is due to the need for coordination of law enforcement activities of the BRICS member nations. The article analyzes the joint system for preventing international crime in the BRICS member nations and concludes that no improvement of this system is possible without appropriate information support for law enforcement based on general principles and approaches. To this end, the necessity of creating a Unified Digital Environment for Law Enforcement Services in the BRICS member nations is substantiated, which implies the speed of achieving the objectives of law enforcement in the BRICS member nations; reduction of corruption risks in this area; as well as automation of individual work processes by replacing a human resource with software. The article describes the concept of a Unified Digital Environment for Law Enforcement Services of the BRICS member nations, substantiates the components that make up its structure. The modern methods of information processing that can be used to build the specified information system are presented. Possible interested users of this environment are highlighted and the capabilities of the Unified Digital BRICS Law Enforcement Services Environment provided to these users are presented.